Progress in the Study of Non-Coding RNAs in Multidifferentiation Potential of Dental-Derived Mesenchymal Stem Cells - Zeng, Biyun; Huang, Junhui (Frontiers in Genetics, 2022)
For decades, the desire for tissue regeneration has never been quenched. Dental-derived mesenchymal stem cells (DMSCs), with the potential of self-renewal and multi-directional differentiation, have attracted much attention in this topic. Growing evidence suggests that non-coding RNAs (ncRNAs) can activate various regulatory processes. Even with a slight decrease or increase in expression, ncRNAs can weaken or even subvert cellular fate. Therefore, a systematic interpretation of ncRNAs that guide the differentiation of DMSCs into cells of other tissue types is urgently needed. In this review, we introduce the roles of ncRNAs in the differentiation of DMSCs, such as osteogenic differentiation, odontogenic differentiation, neurogenic differentiation, angiogenic differentiation and myogenic differentiation. Additionally, we illustrate the regulatory mechanisms of ncRNAs in the differentiation of DMSCs, such as epigenetic regulation, transcriptional regulation, mRNA modulation, miRNA sponges and signalling. Finally, we summarize the types and mechanisms of ncRNAs in the differentiation of DMSCs, such as let-7 family, miR-17∼92 family, miR-21, lncRNA H19, lncRNA ANCR, lncRNA MEG3, circRNA CDR1as and CircRNA SIPA1L1. If revealing the intricate relationship between ncRNAs and pluripotency of DMSCs 1 day, the application of DMSCs in regenerative medicine and tissue engineering will be improved. Our work could be an important stepping stone towards this future.